Principles Of "Hakka Yürüme" In Alevis Of Ardahan (Damal): Beliefs And Practices Concerning To Death - Uyanik, Zeki; Kala, Arif (Journal of Alevism-Bektashism Studies, 2013)
Although death is a universal fact for all human-beings, reactions to death and perceptions of death by peoples may vary according to the cultural environments. Together with birth and marriage, death is among the turning points of human life. Like other turning points, death and ceremonies of funeral are also practiced along with a number of tradition and rituals. In this study we focused on beliefs and religious practices of Alevi community in Ardahan. Preparation of the body for burial, burying the body, traditions relating to after-burial and beverament in Ardahan Alevis are main dimensions of the study.Main methods of this study are participant observations and in-depth interviews. In-depth interviews were conducted with religious leaders (dede) of Alevis, who are living in Damal (a sub-province of Ardahan mainly inhabited by Alevis). In addition to the interviews, funeral ceremony of a member of Alevi community was attended. Because of the fact that there is no previous research in this subject, our study is a pioneering study. Our study is important for also its emphasis on the differences between Alevis and Sunnis in terms of death and funerals.
Keywords: Principles of Hakka Yürüme (death); funeral; Alevis of Ardahan (Damal)